2014
DOI: 10.1089/ham.2013.1114
|View full text |Cite
|
Sign up to set email alerts
|

Rhodiola crenulata- and Cordyceps sinensis-Based Supplement Boosts Aerobic Exercise Performance after Short-Term High Altitude Training

Abstract: . Rhodiola crenulata-and Cordyceps sinensis-based supplement boosts aerobic exercise performance after short-term high altitude training. High Alt Med Biol 15:371-379, 2014.-High altitude training is a widely used strategy for improving aerobic exercise performance. Both Rhodiola crenulata (R) and Cordyceps sinensis (C) supplements have been reported to improve exercise performance. However, it is not clear whether the provision of R and C during high altitude training could further enhance aerobic endurance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 44 publications
(57 reference statements)
0
22
0
Order By: Relevance
“…A systematic review of these studies reveals that Rhodiola preparations exhibit ergogenic, antifatigue and antidepressant properties, indicated by an enhancement of both physical and mental performance. Although contradictory results exist in different studies, most studies show that both R. rosea and R. crenulate are able to enhance physical performance in healthy subjects, indicating an ergogenic effect . Several commercially available R. rosea preparations, such as ADAPT‐232, SHR‐5, and WS 1375, are highly evidenced to benefit burnout patients or subjects with work‐ or stress‐related fatigue after repeated doses or a single dose .…”
Section: Clinical Trialsmentioning
confidence: 99%
“…A systematic review of these studies reveals that Rhodiola preparations exhibit ergogenic, antifatigue and antidepressant properties, indicated by an enhancement of both physical and mental performance. Although contradictory results exist in different studies, most studies show that both R. rosea and R. crenulate are able to enhance physical performance in healthy subjects, indicating an ergogenic effect . Several commercially available R. rosea preparations, such as ADAPT‐232, SHR‐5, and WS 1375, are highly evidenced to benefit burnout patients or subjects with work‐ or stress‐related fatigue after repeated doses or a single dose .…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Studies also found that O . sinensis can increase hypoxia tolerance (Singh et al ., ) and ATP levels on muscle strength, power output and endurance (Chen et al ., ; Kumar et al ., ). Recent studies also demonstrated fascinating potentialities of O .…”
Section: Functional Activities and Mechanisms Of O Sinensismentioning
confidence: 97%
“…Participants took either placebo or a dietary supplement containing 1400 mg R crenulata and 600 mg Cordyceps daily for 2 weeks at an altitude of 2200 m 21 . The study found that participants taking the dietary supplement had significantly better aerobic exercise capacity, longer exhaustive run time, and better maintenance of parasympathetic activities 21 …”
Section: Cordycepsmentioning
confidence: 99%
“…The study found that patients treated with Cordyceps had significantly less incidence of contrast‐induced nephropathy. Chen et al 21 investigated the efficacy of Rhodiola crenulata and Cordyceps supplementation in improving aerobic endurance capacity and exercise performance in 18 male participants during high‐altitude training. Participants took either placebo or a dietary supplement containing 1400 mg R crenulata and 600 mg Cordyceps daily for 2 weeks at an altitude of 2200 m 21 .…”
Section: Cordycepsmentioning
confidence: 99%
See 1 more Smart Citation